Relation between nocturnal symptoms and changes in lung function on lying down in asthmatic children. Issue 3 (March 1991) - Greenough, A; Everett, L; Pool, J; Price, J F
Abstract : Nocturnal symptoms are common in young asthmatic children. Such symptoms may be caused by increased impairment of lung function when they adopt the supine posture. Thirty one children aged 2.8-8.3 years were studied, of whom 20 had asthma (10 with frequent nocturnal symptoms) and 11 had no respiratory problems (control subjects). Peak expiratory flow (PEF) was measured with a Wright's peak flow meter and functional residual capacity (FRC) by a helium gas dilution technique after 30 minutes of lying supine; the values were compared with FRC measured sitting and PEF standing. Peak flow fell significantly on adoption of the supine posture in the asthmatic children, but there was no difference in this fall between the asthmatic children with and without nocturnal symptoms. FRC also fell on adoption of the supine posture, but the decrease in FRC was significant only in the control children and the asthmatic children without nocturnal symptoms. The failure to find a greater fall in PEF or a greater change in FRC on adoption of the supine posture among asthmatic children with nocturnal symptoms suggests that mechanisms other than increased impairment of lung function are responsible for nocturnal asthma.